Oto-neurological manifestation in post COVID-19 patients: a randomized prospective observational study - Singh, Ram Siya; Singh, Sivendra Pratap; Keshri, Sankalp; Prakash, Anand (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Background: The corona virus disease (COVID-19) is caused by severe acute respiratory syndrome corona virus 2 (SARS-CoV-2) and is characterized by symptoms of the lower respiratory tract involvement, such as fever, cough, dyspnea, and chest heaviness. Sensorineural hearing loss (SNHL) is most frequent audio-vestibular symptom described, occurring alone or in association with tinnitus and vertigo. Methods: This study was conducted in COVID-19 tertiary care center Prayagraj. COVID-19 positive patients who were included in moderate to severe category were taken up for the study and data was collected from 1st June 2021 to 1st July 2022 for audiological assessment and presence of equilibrium disorder. All patients were investigated on basis of closed ended questionnaire. Results: Out of 1000 patients incidence of ear heaviness was found in 3.3%., decreased hearing in 0.9%., tinnitus in 1.9%., equilibrium in 0.4% and migraine in 0.4%, which was higher as compared to the normal population but not significant. Conclusions: SARS-CoV-2 infection may cause thrombosis in audiovestibular artery and may alter the blood flow in cochlea and vestibule and cause otoneurological manifestation.